Point-of-care brain magnetic resonance imaging in children with head trauma (BRAINCHILD): Protocol for a prospective observational cohort study - Pradip P. Chaudhari; Kayla Guzman; Jason M. Toliao; Samantha Lozano; Christina Lee; Payal Shah; Frank Gonzalez; Bradley J. De Souza; Ryan Spurrier; Peter A. Chiarelli; Jonathan D. Santoro; Ramón Durazo-Arvizu; et al. (PLoS ONE, 2026)
Background Traumatic brain injury (TBI) is a leading cause of disability and death in children. More than 30% of children presenting to the emergency department (ED) with head trauma undergo brain computed tomography (CT), the standard neuroimaging modality in acute evaluation of intracranial pathology. Conventional magnetic resonance imaging (MRI) provides a non-ionizing alternative with greater sensitivity for certain intracranial injuries but is infrequently used in acute TBI because of limited scanner access and longer scan duration. Rapid brain MRI protocols reduce scan time and can be completed without sedation, with diagnostic accuracy for TBI comparable to CT, yet real-world availability remains limited. Point-of-care, low-field MRI (POC LF-MRI) systems are a recent radiologic advance that are portable, require less infrastructure, and allow bedside neuroimaging, including in critically injured children who cannot be safely transported. However, critical knowledge gaps exist regarding the diagnostic accuracy and feasibility of POC LF-MRI for pediatric head trauma in emergency and critical care settings. Objective Our research aims to (1) determine the accuracy of POC LF-MRI for neuroradiographic TBI and clinically important TBI compared to current clinical standard of care initial neuroimaging, (2) determine the accuracy of POC LF-MRI for neuroradiographic injury progression on repeat neuroimaging, and (3) determine feasibility metrics and balancing measures of POC LF-MRI, including order-to-scan time, scan duration, proportion of incomplete scans, and ED length-of-stay. Methods We will conduct a prospective, single-center, observational diagnostic accuracy cohort study of children 7–17 years old with blunt head trauma who undergo standard-of-care neuroimaging. Children with MR-unsafe implants or metallic shrapnel and wards of the state will be excluded. POC LF-MRI will be obtained within a reasonable time window of clinical neuroimaging, with a flexible window up to 72 hours, either in the ED, inpatient unit, or intensive care unit (ICU). The primary outcome is neuroradiographic TBI, defined as any traumatic intracranial finding on neuroimaging. Secondary outcomes include clinically important TBI (defined as TBI-related neurosurgical intervention, endotracheal intubation >24 hours, death, or ≥2-night hospitalization) and neuroradiographic injury progression on repeat neuroimaging (yes/no). Feasibility outcomes include order-to-scan time, scan duration, proportion of incomplete scans, and ED length of stay, along with other operational and balancing measures. Accuracy will be determined using imaging-level analyses comparing POC LF-MRI with clinical standard-of-care neuroimaging, reporting sensitivity, specificity, predictive values, and likelihood ratios with 95% confidence intervals for neuroradiographic TBI, clinically important TBI, and neuroradiographic injury progression, including predefined non-inferiority criteria for sensitivity, subgroup analyses, descriptive analyses of feasibility metrics, and exploratory analyses addressing incomplete imaging and missing data. Results The project was funded in 2024, and enrollment will be completed in July 2026. Data analyses are expected to be completed by December 2026, and the primary study results will be submitted for publication in 2027. Conclusions This study will evaluate accuracy and feasibility for POC LF-MRI in an important subset of pediatric trauma patients and will provide preliminary data to inform future multicenter studies evaluating POC LF-MRI for children with head trauma.